Management of salt affected soils for crop production - Gupta, Dipak Kumar; Choudhary, Kamla K.; Shukla, A. K. (Indian Farming, 2018)
Salinity and alkalinity of soil is one of the most severe abiotic factors limiting agricultural production in arid and semi-arid regions of the world. In India, under different agro-ecological regions about 6.74 million ha area is salt affected (saline, saline-sodic and sodic soils) which is severely affecting crop yield. Saline and sodic soils have different characteristics and thus require different strategies for management. There is need for use of efficient technologies for managing these problematic soils for enhancing crop yield especially in arid and semi-arid regions. Among different technologies, growing of salt-tolerant crops; application of amendments (gypsum, organic manure and green manuring) and surface- and sub-surface drainage is most effective in managing sodic as well as saline soils in arid and semi-arid regions.